Development of CdTe-based nuclear radiation sensors and related devices - Volodymyr Gnatyuk; Valery Sklyarchuk; Toru Aoki; Akifumi Koike; Wisanu Pecharapa (My University, 2018)
The portable nuclear radiation sensor devices have been developed based on the compact spectrometers equipped with the CdTe-based X/γ-ray detectors in a stacked mode. The stacks were assembled using four Ni/CdTe/Au Schottky diodes mounted on separate thin printed circuit boards (PCB) electrically connected in parallel to provide higher detection efficiency and then were connected to the common electrodes and fixed on the small PCB. The Ni/CdTe/Au diode detectors with a Schottky barrier and near Ohmic contact at the Ni-CdTe and Au-CdTe interfaces, respectively, were created using the Ar-ion bombarding technique. The fabricated stacks of four Ni/CdTe/Au diode detectors were tested by measuring of 137Cs isotope spectra. Energy resolution of Schottky diode detectors, mounted in a stacked mode, was slightly lower (∼ 3.0%@662 keV) compared with the separate detectors however, the number of counts in the spectra significantly increased evidencing an increase in detection efficiency (sensitivity) of the stacks. The fabricated portable sensors can be employed for identification and localization of radioactive sources in environment monitoring and high-energy radiation spectroscopic measurements.
Keywords: Cadmium telluride photovoltaics; Ohmic contact; Particle detector; Nuclear Radiation; Radioactive source; Advanced Semiconductor Detectors and Materials